1991
DOI: 10.1128/aac.35.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the antibiotic sparsomycin with the ribosome

Abstract: Phenol-alanine-sparsomycin, a derivative of sparsomycin carrying a p-hydroxy-benzyl function easily labeled by iodination, has been used to study the interaction of this drug with the ribosome. Our study indicated that the binding of the drug to the ribosome is sensitive to trichloroacetic acid and is equally affected by disintegration of the particle after RNase and protease treatments. The ribosome is not irreversibly inactivated, and the chemical structure of the drug is not affected by interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
(18 reference statements)
1
11
0
1
Order By: Relevance
“…This is understandable since the conjugated tail of SPAR overlaps with the aminoacyl‐moiety of an A‐tRNA (Fig. 4B) and thus would prevent binding not only of A‐tRNA, but also CAM and lincomycin in agreement with previous reports 34,39 . The binding site of SPAR in the D50S structures in contrast spans across the P site and does not encroach on the A site (Fig.…”
Section: Sparsomycin Interaction With A2602 Promotes Translocationsupporting
confidence: 89%
See 1 more Smart Citation
“…This is understandable since the conjugated tail of SPAR overlaps with the aminoacyl‐moiety of an A‐tRNA (Fig. 4B) and thus would prevent binding not only of A‐tRNA, but also CAM and lincomycin in agreement with previous reports 34,39 . The binding site of SPAR in the D50S structures in contrast spans across the P site and does not encroach on the A site (Fig.…”
Section: Sparsomycin Interaction With A2602 Promotes Translocationsupporting
confidence: 89%
“…Sparsomycin (SPAR), a nucleoside analog of uracil (Fig. 4A) produced by Streptomyces sparsogenes , is a potent inhibitor of peptidyltransferase activity in bacteria, archaea, and eukaryotes (reviewed by Lazaro et al 34 ). SPAR has been crystallized together with tRNA mimics in complex with both archaeal (H50S) 9,35 and bacterial (D50S) 36 ribosomes (Table 1).…”
Section: Sparsomycin Interaction With A2602 Promotes Translocationmentioning
confidence: 99%
“…We stored sparoxomycin and its analogues (3)(4)(5)(6)(7) in the dark after their recrystallization from MeOH, because the trans double bond tended to easily isomerize to the cis-isomer in a solution.…”
Section: Synthesis Of Sparsomycin and Its Alkyl Analoguesmentioning
confidence: 99%
“…The biological activity resulted from its ability to inhibit the peptide bond-forming step of protein biosynthesis by interacting with the large ribosomal subunit. [7][8][9][10] These potentially important biological activities have made 3 an attractive target for a potential antineoplastic compound. 11) Since thê rst synthetic study of sparsomycin in 1976, 12) synthetic studies of sparsomycin, [13][14][15] total synthesis, [16][17][18] biosynthesis, 19,20) and structure-activity relationship studies [21][22][23][24][25][26][27] have been widely reported.…”
mentioning
confidence: 99%
“…The biological activity of sparsomycin is the result of its ability to inhibit the peptide bond-forming step of protein biosynthesis by interacting with the large ribosomal subunit in a poorly understood, complex manner (16)(17)(18)30). Although the clinical use of sparsomycin is precluded due to drug-related retinopathy, a number of more potent analogs have been prepared which may prove useful in cancer chemotherapy (16). One of the novel components of the sparsomycin molecule is (E)-3-(2,4-dioxo-6-methyl-5-pyrimidinyl)acrylic acid (UCA).…”
mentioning
confidence: 99%